Media Sosial dan Komunikasi Krisis: Pelajaran dari Industri Telekomunikasi di Indonesia - Dani Akhyar; Arum Sekar Pratiwi (ULTIMA Comm, 2019)
This article discusses the communication crisis that occurs and is done through social media. The two cases chosen were from the telecommunications industry. The speed and complexity of the telecommunications industry is the main reason for choosing the main theory in this study, which is the Situational Crisis Communication Theory (SCCT) developed by Coombs (2007). The telecommunications industry is one of the industries that vulnerable to crisis, moreover when telecommunications products such as smartphones and the internet have become one of the basic needs of every person. Using qualitative methods, the results of this study indicate that the application of SCCT in the telecommunications industry requires some special records. First, the need for a crisis marking system that is sensitive to the emergence of a potential crisis. Second, the response system should be more responsive because of the behavior of telecommunications customers who tend to be impatient and quickly spread negative news with their social media. Keywords: situational crisis communication theory, crisis communication, telecommunication industry